Gratitude Journal as an Instrument to Increase the Level of Gratitude among Adolescent in Ambon During COVID-19 - Theophanny Paula Theresia Rampisela; Yulian Hermanus Wenno (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2023)
COVID-19, which has plagued the world since 2020, has brought changes in the order of human life globally, and ultimately has an impact on the psychological state of individuals, including teenagers. The aim of this study is to find the differences between students’ gratitude score before and after the implementation of writing gratitude journal regularly. Participants on this study was 20 adolescents in Ambon City Maluku Indonesia, consists of 6 boys and 14 girls. The participants age was between 15-16 years old. Quantitative Method with experimental design used in this study. From the results, it was found that the significant value in the table paired samples correlations was 0.418, meaning that there are relationship between the results of the pre-test and post-test because the value was > sig. 0.05. Although the increase in the value of gratitude among adolescents in Ambon is not too large and increases their classification to be included in the criteria for groups that have sufficient gratitude scores, the important thing explained in implementing gratitude education actually lies in its aim to inspire students that it is important to be grateful in all circumstances. and it's not just about saying thank you or showing grateful behavior.